MEMPERTAHANKAN RETENSI PELANGGAN YANG DIPENGARUHI OLEH KEPUASAN PELANGGAN KUALITAS PELAYANAN DAN KEPERCAYAAN PELANGGAN PADA PT PIRANTI BERKAH TRAVELINDO - Wiryono, Setyo Legowo; Supriyadi, Andhi; Putri, Julian Andriani (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine and explain the influence of customer satisfaction, service quality and customer trust spatially and jointly on customer retention. The research was conducted using quantitative methods. The sample was 90 customers of PT. Piranti Berkah Travelindo Tool taken using the Census technique. The data collection technique uses a questionnaire, and the data is tested and analyzed using multiple linear regression analysis with SPSS version 20. Based on the research data analysis, it can be concluded that (1) customer satisfaction has a positive and significant effect on customer retention, (2) service quality has a positive effect and significant to customer retention (3) customer trust has a positive and significant effect on customer retention, (4) customer satisfaction, service quality and customer trust together have an effect on customer retention Keywords: Customer Satisfaction, Service Quality, Trust and Customer Retension